A Randomized Controlled Biofeedback Intervention Study On Heart Rate Variability In Unemployed Subjects - Petrowski, Katja; Wendt, Katharina; Wichmann, Susann; Siepmann, Martin (Journal of Depression And Therapy, 2017)
Background: Unemployment is a chronic stressor which is associated with higher levels of impaired physical and mental wellbeing, e.g. reduced heart rate variability (HRV) and decline in self-esteem and self-efficacy. The present study investigated the effectivity of a HRV-biofeedback-training in increasing HRV and general self-efficacy. Method: A total of n = 22 unemployed individuals with adjustment disorder participated in this study (14 females, mean ages 42.53 ± 8.88 years). All participants performed randomized the “stress tests” for heart rate (HR) and HRV assessment: timed breathing, d2-attention-stress-test and math-test drawn from the Trier Social Stress Test (TSST). Four sessions HRV-biofeedback à 20 min within 2 weeks were administered. HR and HRV were assessed before and after biofeedback training. ECG preprocessing and analysis were performed with the Stressball software program (BioSign GmbH, Ottenhofen, Germany). The RMSSD time domain measure was calculated as HRV index. Clinical outcome measures were the ADNM total score and the general self-efficacy scale (GSE). Results: Participants were well matched in terms of demographic and clinical characteristics. ANOVA didn’t demonstrate significant time x group interaction effects neither for HRV parameters (HR, RMSSD) nor for psychological parameters (ADNM, GSE). Conclusion: Our findings do not indicate that HRV-biofeedback can increase HRV nor general self-efficacy in unemployed subjects with adjustment disorder. Implications for future studies are discussed.
Keywords: heart rate variability; RMSSD; biofeedback; unemployment